Attention and the motion aftereffect. Issue 12 (December 2019) - Morgan, Michael J; Solomon, Joshua A
We measured the effects of attentional distraction on the time course and asymptote of motion adaptation strength, using visual search performance (percent correct and reaction time). In the first two experiments, participants adapted to a spatial array of moving Gabor patches, either all vertically oriented (Experiment 1) or randomly oriented (Experiment 2). On each trial, the adapting array was followed by a test array in which all of the test patches except one were identical in orientation and movement direction to their retinotopically corresponding adaptors, but the target moved in the opposite direction to its adaptor. Participants were required to identify the location of the changed target with a mouse click. The ability to do so increased with the number of adapting trials. Neither search speed nor accuracy was affected by an attentionally demanding conjunction task at the fixation point during adaptation, suggesting low-level (preattentive) sites in the visual pathway for the adaptation. In Experiment 3, the same participants were required to identify the one element in the test array that was slowly moving. Reaction times in this case were elevated following adaptation, but once again there was no significant effect of the distracting task upon performance. In Experiment 4, participants were required to make eye movements, so that retinotopically corresponding adaptors could be distinguished from spatiotopically corresponding adaptors. Performance in Experiments 1 and 2 correlated positively with reaction times in Experiment 3, suggesting a general trait for adaptation strength.